Re‐emergence of a genotype VIII virulent Newcastle disease virus isolated from Chinese game fowl after 13 years. Issue 2 (5th February 2019) - Wei, Tianchao; Deng, Qiaomu; Zhai, Guosheng; He, Chengwei; Li, Haiqiong; Zhang, Yuanqin; Zeng, Rongling; Mo, Meilan; Huang, Teng; Wei, Ping
Abstract: Circulation of dominant genotypes VI and VII of Newcastle disease virus (NDV) is causing significant economic losses to the poultry industry in China. However, reports of Newcastle disease (ND) outbreaks caused by genotype VIII strains of NDV are rare. In this study, a virulent genotype VIII strain of NDV, designated GXGB2011, was isolated from a vaccinated game fowl flock showing clinic signs of infection in Pinxiang county, Guangxi, China. The whole genome of the isolate was completely sequenced and was found to be comprised of 15, 192 nucleotides (nt), encoding the six structural proteins in the order of 3′‐NP‐P‐M‐F‐HN‐L‐5′. The pattern of cleavage site 112 RRQKR↓F 117 in the fusion (F) protein and the intracerebral pathogenicity index (ICPI) value of 1.5 showed that the strain GXGB2011 was a velogenic NDV. The results of the challenge experiment with the 5‐week‐old SPF chickens showed that the strain was highly pathogenic with 100% morbidity and mortality of the challenged birds. Based on the detection of virus in different organs of the infected birds, the highest viral load in caecal tonsils was observed and viral levels in immune organs were higher than those in the respiratory organs. Bayesian reconstruction of complete genomes based on the sequences of 66 NDV reference strains showed that the strain belonged to the genotype VIII of NDV. Phylogenetic analysis showed that the strain was more closely related to the foreign strains gamefowl/U.S.(CA)/24225/98, 1ITTY94060 and IT‐147/94 rather than to the first domestic strains of the emergence genotype VIII in Qinghai, China during 1979–1985. In summary, the results of the study demonstrated the re‐emergence of a highly pathogenic virulent isolate of genotype VIII of NDV. These results indicate the risk that this genotype VIII of NDV may spread to commercial chickens from game fowl.